IV International Golden Horde Forum » - E.G. Sayfetdinova (Золотоордынское обозрение, 2015)
Usmanov Center for Research on the Golden Horde and Tatar Khanates (Sh.Marjani Institute of History of Academy of Sciences of the Republic of Tatarstan) has once again become the organizer of a major international academic event aimed at illuminating source studies on the history of the Golden Horde and Turko-Tatar khanates. March 17–18, 2015, Kazan hosted the fourth international Golden Horde forum, which was attended by representatives from 11 countries: Russia, Great Britain, Netherlands, USA, Poland, Ukraine, Turkey, Finland, Kazakhstan, Serbia, and Bulgaria. Three international conferences and round table were held within the forum. The first research conference – “Source Study of the Golden Horde History: Traditions and Innovations” – was devoted to the important issues of source study of the history of the Golden Horde and the Turko-Tatar khanates. The second research conference was dedicated to the “Minting and Circulation of Money in the Golden Horde and Turko-Tatar Khanates in the Light of Source Studies”. The third conference was devoted to the theme: “The Crimean Khanate in International Diplomacy”. The theme of the round table of the fourth international Golden Horde forum was: “The Gene Pool of the Turkish Populations as a Historical Source”.